EFFECT OF BAHIAGRASS COVER ON THE CHEMICAL PROPERTIES OF AN ULTISOL AT DIFFERENT LEVELS OF SLOPE IN UMUDIKE, NIGERIA - Ojimgba ONWUCHEKWA; Mgbeahuru CHIBUIHEM (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The effect of Bahia grass (Paspalum notatum) on the chemical properties of an ultisol at different levels of slope was carried out in Umuahia, Southeastern Nigeria. The use of Paspalum notatum has attracted considerable research attention with respect to forage production and erosion control. Little information is available on the influence of this grasscover management on soil chemical properties. This research work was carried out at different levels of slope planted with Paspalum notatum (4%, 20% and 33%) and also on bare soil. The study has shown that the slopes planted with Paspalum notatum gave significantly higher results of the chemical properties than the open adjacent bare soil. In all the parameters considered in this study, the values obtained in 4% slope was higher than those obtained in 20% as well as 33% and the bare soil, in the following significant order: 4%> 20% > 33% > Bare soil. However, 4% slope had higher values of phosphorus (P) than the similar values of 33% and 20%, while Bare soil gave the least value in the order: 4%> 33% = 20% > Bare soil. Also, the exchangeable acidity (H+ and Al3+) values were significantly ( P<0.05) higher in bare soil than in those slopes planted with Paspalum notatum. This result also pointed to the fact that the pH of the soils planted with Paspalum notatum gave higher values than the corresponding bare soil. Therefore, Paspalum notatum improved very highly the chemical properties of the tropical soils, whereas bare soil had no such effect.